(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2021)
The essay traces the history of some major aristocratic families active in the Lombard territory between the 9th and 10th centuries, evaluating the breadth and articulation of the political spaces, thus integrating their action at the service of the kingdom, the distribution of the land patrimony and the foundation of churches and abbeys. From these family‐histories, a slow but evident transition from a carolingian to a post‐carolingian political system emerges with particular clarity. In the 9th century, aristocratic families derive their power first of all from the service to the king, exercised in different cities and regions, and they use the local bases of power as a way to activate links of political communication with the royal power. This dimension does not disappear, but we see a change towards a different system of domination, in which both the patrimonial base of the family and its presence in the territory become fundamental, to define a political configuration that takes on fully regional connotations and in many cases moves away from the cities.